Cardiac risk in the treatment of breast cancer: assessment and management - Valachis A (Dove Medical Press, 2015)
Antonis Valachis,1 Cecilia Nilsson2 1Centre for Clinical Research Sörmland, Uppsala University, Eskilstuna, Sweden; 2Center for Clinical Research, Västmanlands County Hospital, Västerås, Sweden Abstract: As the number of long-term breast cancer survivors has increased, the side effects of adjuvant cancer therapy, such as cardiac toxicity, remain clinically important. Although the cardiac toxicity due to anthracyclines, radiotherapy, or trastuzumab is well-documented, several issues need to be clarified and are the subjects of extensive ongoing clinical research. This review summarizes the incidence of cardiac toxicity due to breast cancer adjuvant therapy and highlights the current trends in early detection and management of cardiac toxicities. Keywords: adjuvant, anthracyclines, cardiac toxicity, radiotherapy, trastuzumab